Pandangan Mufasir Indonesia Terhadap Isu-Isu Hak Asasi Manusia - Mujahid, Ahmad (Mutawatir : Jurnal Keilmuan Tafsir Hadith, 2019)
This article argues that the attitude of Indonesian mufassir is not always parallel in respond to the concept of Human Rights. This is shown from our discussion of three contextual issues in human rights: freedom of religion, freedom to find a mate, and death sentence, which are exemplified by comparing to the three Indonesian mufassir: Hamka’s Tafsir al-Azhar, Hasbi ash-Shiddieqy’s Tafsir al-Nur and Tafsir al-Bayan, and Quraish Shihab’s Tafsir Al-Mishbah. The article concludes: First, in respond to the human rights issues, Indonesian commentators tend to be responsive. All three exegetes denied those who claimed that Islam was spread with violence and those who opposed the death penalty. Second, on the relationship between human rights and Islam, the commentators have similarities and differences with human rights. Among these similarities, for example, is the issue of religious freedom. As for the issue of freedom to choose a mate and a death sentence, they are taking a different position from human rights. On the issue of death penalty, the commentators emphasize to not only looking from the side of the killer, but also from the right of the murder.